Framing and sources: News on environmental justice in Bangladesh - Jahnnabi Das (Asia Pacific Network, 2019)
With the rapid economic development and growing population, Bangladesh is one of the most environmentally vulnerable countries in the world. In this country, news reporting of environmental issues is vibrant and vigorous, although it attracts scant scholarly attention. In fact, environmental journalism in this South Asian country is one of the least studied topics in the area of journalism research. The current study attends to this country and examines news sources in two newspapers in Bangladesh, focusing on their coverage of river systems and climate change in 2009 and 2015. This study explores various sources, such as politicians, bureaucrats, activists, and citizens, and the patterns of emphasis in the news by using these sources to understand the framing of river degradation and climate change. The aim here is to illustrate the journalists’ influence in defining these environmental problems against various news sources and social actors. The qualitative analysis reveals an emphasis on political and bureaucratic sources in 2009 and on expert and citizen sources in 2015. Additionally, the analysis also demonstrates that the journalists—as actors in defining the reality—have exerted ‘influence’ on accentuating environmental concerns by shifting their source emphasis over time from politicians and bureaucrats to experts and citizens. Through this emphasis, they uphold the discourse of environmental justice in varied contexts.